Growth, gas exchange, and mineral nutrition of 'Wonderful' pomegranate irrigated with saline water - Youping Sun; Genhua Niu; Joseph G. Masabni (Technology in Horticulture)
'Wonderful' pomegranate (Punica granatum) is currently the industry-standard cultivar, accounting for more than 90% of all commercially planted trees. The purpose of this study was to determine the response of 'Wonderful' pomegranate trees to a range of salinity by irrigating them with a nutrient solution at an electrical conductivity (EC) of 1.2 dS·m−1 (control) or one of two saline solutions at EC of 5.0 (EC 5) or 10.0 dS·m−1 (EC 10) in two rounds of treatments. Pomegranate plants with saline solution treatments had no or minimal foliar salt damage. However, EC 10 reduced shoot dry weight (DW) by 15% relative to the control in the first round, and both EC 5 and EC 10 reduced shoot DW by 13% and 31%, respectively, in the second round compared to the control. The concentration of sodium (Na) was ≤ 1 mg·g−1 in the leaves and stems in all treatments but was much higher in the roots in EC 5 and EC 10. The concentration of chloride (Cl) in the leaves, stems, and roots increased by 36%−90%, 101%−156%, and 254%−299%, respectively, in EC 5 and EC 10 compared to the control. Salinity reduced the concentration of all macronutrients and some micronutrients, especially in the leaves, compared to the control. However, there was no or minimal effect on leaf gas exchange and SPAD readings. These results indicate that 'Wonderful' pomegranate is highly tolerant to salinity and has a strong ability to exclude Na accumulation in the leaves, thus avoiding salt damage.